Pencegahan Plagiarisme Akademis Perspektif Al-Qur’an - Azmi Afghani; Arich Hawary Anshorullah; Abdul Rauf Haris (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) ZAD, Cianjur, indonesia, 2026)
Plagiarism is one of the forms of misuse of human intellect that has increasingly occurred among students as well as senior academics. This act not only violates academic ethics, but also contradicts the moral values of the Qur’an and the objectives of Islamic law (maqāṣid al-sharī‘ah), particularly ḥifẓ al-māl (the protection of wealth), since written works are considered a form of intellectual property that must be respected. In Islam, plagiarism is also contrary to the concept of copyright or ḥaqq al-taʾlīf. This study aims to offer solutions for preventing plagiarism based on Qur’anic ethics through the approach of maqāṣid al-sharī‘ah in order to establish an academic culture grounded in integrity. The research employs a thematic conceptual study method through a literature review of various sources related to Qur’anic ethics, plagiarism, intellectual property rights, and maqāṣid al-sharī‘ah. The findings reveal six main solutions for plagiarism prevention: honesty in words and actions, awareness that taking the rights of others is a prohibited act, trustworthiness in knowledge, honesty in conveying facts, responsibility in managing knowledge, and fairness in scholarly endeavors. The novelty of this study lies in the integration of Qur’anic ethics with maqāṣid al-sharī‘ah as a preventive approach to plagiarism. The implications of this research highlight the importance of strengthening academic policies based on Islamic values in order to protect intellectual rights, prevent losses caused by plagiarism, and foster a scholarly culture that is honest, trustworthy, and characterized by integrity.